ANALISIS KOMPONEN KEBUGARAN JASMANI DAN SOLUSINYA DILIHAT DARI SARANA DAN PRASARANA PENDIDIKAN KELAS V DI SD PAB 12 SAMPALI - Suyono; Fadillah Putri Adeana; Devita Aulia Putri; Usna Aulia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This article discusses the components of physical fitness for fifth grade students at SD PAB 12 Sampali, with a focus on the facilities and infrastructure available. The three main aspects studied are: first, the physical fitness component based on existing facilities and infrastructure; second, the obstacles faced related to the physical fitness component; and third, the solutions provided by physical education teachers to overcome this problem. This research uses descriptive qualitative methods, with data collection techniques through interviews, observation and documentation. The research results show that the components of physical fitness in terms of facilities and infrastructure include muscle strength, speed and muscle endurance. Obstacles found included a lack of physical education facilities and infrastructure, as well as a lack of student interest in sports. Solutions proposed by physical education teachers include adapting activities to students' wishes and modifying sports equipment to overcome existing deficiencies.